Early aspirin initiation following heart transplantation is associated with reduced risk of allograft vasculopathy during long‐term follow‐up. Issue 12 (7th December 2017) - Peled, Yael; Lavee, Jacob; Raichlin, Eugenia; Katz, Moshe; Arad, Michael; Kassif, Yigal; Peled, Amir; Asher, Elad; Elian, Dan; Har‐Zahav, Yedael; Shlomo, Nir; Freimark, Dov; et al.
Abstract: Aim: Cardiac allograft vasculopathy (CAV) is a major cause of morbidity and mortality after heart transplantation (HT). Enhanced platelet reactivity is a contributing factor. We aimed to investigate the association between early initiation of aspirin therapy post‐HT and the 15‐year risk of the development of CAV. Methods: We studied 206 patients who underwent HT between 1991 and 2016. Multivariate Cox proportional hazards regression modeling was employed to evaluate the association between early aspirin initiation and the long‐term risk of CAV. Results: Ninety‐seven patients (47%) received aspirin therapy. At 15 years of follow‐up, the rate of CAV was lowered by sixfold in patients treated with aspirin compared with the non‐treated patients: 7% vs 37% (log‐rank P ‐value<.001). The corresponding rates of the combined end‐point of CAV or death were also lower in patients treated with aspirin, compared with the non‐treated patients: 42% vs 78% (log‐rank P  < .001). Consistently, multivariate analysis showed that early aspirin therapy was associated with a significant 84% ( P  < .001) reduction in CAV risk, and with a corresponding 68% ( P  < .0001) reduction in the risk of the combined end‐point of CAV or death. We further validated these results using a propensity score‐adjusted Cox model. Conclusions: Early aspirin initiation is independently associated with a significant reduction in the risk of CAV.